PERBEDAAN TINGKAT KESEGARAN JASMANI SISWA SMA NEGERI 3 MANDAU DAN SISWA SMA NEGERI 9 MANDAU KABUPATEN BENGKALIS - Dwi Indah Permata Sari; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is students who experience fatigue during sports hours, and even students who do not sweat when sports hours are over. This type of research is quantitative descriptive research, which is analyzing data by describing or describing data that has been collected as it is without intending to make conclusions that apply to the public or generalization. The purpose of this study was to determine differences in the level of physical fitness of students of SMA Negeri 3 Mandau and SMA Negeri 9 Mandau students in Bengkalis Regency. The population in this study were male students of class XI MIPA from SMA 3 Mandau and SMA Negeri 9 Mandau Bengkalis Regency, while the total sample was 108 students. The sampling technique is using Proportionate Stratified Random Sampling, which is if the population has elements that are not homogeneous and proportionally distributed. The instrument in this study was the TKJI test for ages 16-19 years. Based on the research findings and discussion of the results of the study it can be concluded as follows: There are Differences in the Level of Physical Freshness of Students of SMA 3 Mandau and SMA Negeri 9 Mandau Students in Bengkalis Regency. this is evidenced by the results of research that t. table <t. arithmetic or 1,980 <8,47 at the significant level of 5%. Where the level of physical fitness of students of SMA Negeri 3 Mandau is better than that of SMA Negeri 9 Mandau students because SMA Negeri 3 Mandau students walk more to school this certainly makes students do a lot of movement activity and makes students' physical fitness healthier. While the students of SMA Negeri 9 Mandau use more vehicles to go to school, so that students do not do a lot of movement activities and make students' physical fitness disturbed.Keywords: Difference, Physical Fitness